2011
DOI: 10.1007/s10546-011-9608-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Numerical Simulations of Extremely Large Atmospheric Boundary-layer Heights over an Arid Region in North-west China

Abstract: Over arid regions in north-west China, the atmospheric boundary layer can be extremely high during daytime in late spring and summer. For instance, the depth of the observed convective boundary layer can exceed 3,000 m or even be up to 4,000 m at some stations. In order to characterize the atmospheric boundary-layer (ABL) conditions and to understand the mechanisms that produce such an extreme boundary-layer height, an advanced research version of the community weather research and forecasting numerical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
(28 reference statements)
0
12
0
2
Order By: Relevance
“…For the vegetated land surface, the model response in ABL height to initial soil moisture is larger than for bare soil. At lower soil saturation (S w = 0.2), the simulated maximum ABL height for bare-soil/vegetation is approximately around 3/4 km for both models, typical for arid regions [33,34]. The higher ABL heights for vegetated surface results from its lower albedo, as explained earlier.…”
Section: Abl Quantitiesmentioning
confidence: 50%
“…For the vegetated land surface, the model response in ABL height to initial soil moisture is larger than for bare soil. At lower soil saturation (S w = 0.2), the simulated maximum ABL height for bare-soil/vegetation is approximately around 3/4 km for both models, typical for arid regions [33,34]. The higher ABL heights for vegetated surface results from its lower albedo, as explained earlier.…”
Section: Abl Quantitiesmentioning
confidence: 50%
“…In flat terrain typical ABL, heights are between 1 and 2 km, while the observed ones are mostly between 2 and 3 km above ground, which is typical for mountainous terrain (e.g., Kossmann et al 1998). Ma et al (2011) observed PBL heights exceeding 4 km in May 2000 close to the Tibetian Plateau over Dunhuang in China, which is located about 800 km to the southwest of the study region.…”
Section: Vertical Structure Of the Tropospherementioning
confidence: 77%
“…It can be seen from Figure 9 that a perfectly mixed ABL existed at the location of the radiosonde radar and the depth of the convective boundary layer was about 2 km. During the observation campaign, the midday ABL at the location of the radiosonde radar could exceed 3 km or even higher (measurements are not shown), which was a result of vigorous turbulent mixing in the Gobi Desert [28]. However, due to the cold-lake effect of Bosten Lake, the lakeshore atmospheric turbulent mixing was inhibited.…”
Section: Gps Sonde Radiosondementioning
confidence: 99%